Self-regulation of students in overcoming the psychological consequences of the influence of information technology (Texas Journal of Medical Science, 2025)
he problem of professional self-determination of an individual has aroused and continues to arouse wide interest from scientists. And this is far from accidental. Professional formation and development are inextricably linked with professional self-determination, which is one of the significant factors of professional success. The current situation in society brings its own peculiarities to the process of professional self-determination. Changes in the system of values and priorities, the uncertainty of external social guidelines make this process even more difficult. In the context of the dynamic development of the labor market, the rapid change of existing professions and the emergence of new types of professional activities, the issues of professional self-determination of schoolchildren and students are particularly acute both theoretically and practically.